Use of Seatbelts and Observable Factors among Public Transport Drivers in Addis Ababa, Ethiopia - Semegnew Takele; Yifokire Tefera; Teferi Abegaz; Hailemichael Mulugeta (Journal of Advanced Transportation)
Wearing of proper seatbelt while driving is scientifically proven to protect from severe and fatal injuries. The aim of this study was to assess the status of proper seatbelt use and observable factors among public transport drivers in Addis Ababa, Ethiopia. The study conducted an inside vehicle observation study among 600 public transport vehicles in Addis Ababa, Ethiopia, from January to February 2017. Sample vehicles were randomly selected from ten arterial and ten collector road networks. This study used an observational checklist for data collection and logistic regression analysis to find the associated variables with improper seatbelt use. The odds ratio with a 95% CI and a p-value of <0.05 were considered for the statistically significant association. The prevalence of proper seatbelt use was 47.5% [95% CI (43.0–51.3)]. Khat chewing [AOR: 2.41, 95% CI (1.04–5.60)], engaged in driving distraction activities [AOR: 2.93, 95% CI (2.08, 4.13)] and being city bus drivers [AOR: 1.66, 95% CI (1.09, 2.52)], were significantly associated with improper seatbelt use. The actual rate of proper seatbelt use among public transport drivers in Addis Ababa was very low compared with the officially known report. Drivers’ behavior and being drivers of large-sized vehicles were associated with improper seatbelt use.